Mutations in emerging variant of concern lineages disrupt genomic sequencing of SARS-CoV-2 clinical specimens. (January 2022) - Kuchinski, Kevin S.; Nguyen, Jason; Lee, Tracy D.; Hickman, Rebecca; Jassem, Agatha N.; Hoang, Linda M.N.; Prystajecky, Natalie A.; Tyson, John R.
Highlights: Amplicon sequencing methods are widely used for SARS-CoV-2 genomics. Amplicon sequencing is disrupted by mutations in emerging SARS-CoV-2 lineages. Current protocols require immediate updates to address these mutations. Routine updates to protocols will be necessary as SARS-CoV-2 continues to evolve. We provide a bioinformatic and laboratory approach for updating sequencing protocols. Abstract: Mutations in emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineages can interfere with laboratory methods used to generate viral genome sequences for public health surveillance. We identified 20 mutations that are widespread in variant of concern lineages and affect widely used sequencing protocols by the ARTIC network and Freed et al. Three of these mutations disrupted sequencing of P.1 lineage specimens during a recent outbreak in British Columbia, Canada. We provide laboratory validation of protocol modifications that restored sequencing performance. The study findings indicate that genomic sequencing protocols require immediate updating to address emerging mutations. This work also suggests that routine monitoring and protocol updates will be necessary as SARS-CoV-2 continues to evolve. The bioinformatic and laboratory approaches used here provide guidance for this kind of assay maintenance.